Case Report: Challenges of Non-Invasive Prenatal Testing (NIPT): A Case Report of Confined Placental Mosaicism and Clinical Considerations - Bonanni, Giulia; Trevisan, Valentina; Zollino, Marcella; De Santis, Marco; Romanzi, Federica; Lanzone, Antonio; Bevilacqua, Elisa (Frontiers in Genetics, 2022)
Since the introduction of cell-free (cf) DNA analysis, Non-Invasive Prenatal Testing (NIPT) underwent a deep revolution. Pregnancies at high risk for common fetal aneuploidies can now be easily identified through the analysis of chromosome-derived components found in maternal circulation, with the highest sensitivity and specificity currently available. Consequently, the last decade has witnessed a widespread growth in cfDNA-based NIPT use, enough to be often considered an alternative method to other screening modalities. Nevertheless, the use of NIPT in clinical practice is still not devoid of discordant results. Hereby, we report a case of confined placental mosaicism (CPM) in which a NIPT false-positive result for trisomy 13 required not only amniocentesis but also cordocentesis, to rule out the fetal aneuploidy, with the additional support of molecular cytogenetics on placental DNA at delivery. Relevant aspects allowing for precision genetic diagnosis and counselling, including the number of analysed metaphases on the different fetal cells compartments and a repeated multidisciplinary evaluation, are discussed.